Pengembangan Aplikasi Perpustakaan Berbasis Website untuk Meningkatkan Layanan Informasi di SMK - Perdana, Daniel Riko Putra; Handayani, Sri; Kholil, Moenawar (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2025)
This research aims to develop a web-based library application to enhance the efficiency of information services at SMK PGRI 1 Surakarta. The study employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) within a Research and Development (R&D) approach. Data were collected through observation, interviews, and documentation related to the existing manual library system. The application was developed using PHP, HTML, CSS, and MySQL and implemented on a local server using XAMPP. Key features included multi-level login, online book catalog, transaction history, and automatic reporting. Usability testing was conducted with librarians and students, while expert validation involved media, content, and field practitioners. Results showed that the application significantly improved service efficiency by reducing transaction time by 50% and enhancing access to book information. The validation score averaged 86%, indicating that the system is feasible for use. The study concludes that the application supports digital transformation and strengthens literacy services in vocational education environments.